Cardiovascular damage due to COVID-19: what do we need to know? - Nascimento,Cristian Rodrigues do (2021)
SUMMARY Severe Acute Respiratory Syndrome Coronavirus 2 is part of the Cononaviridae family and is the causative agent of the 2019 (Covid-19) Coronavirus pandemic declared by the World Health Organization in March, 2020. This virus has a high rate of transmission, affecting several individuals, and has caused thousands of deaths. The clinical manifestations of Severe Acute Respiratory Syndrome Coronavirus 2 infection are not restricted only to the respiratory tract, and there is an express involvement of the cardiovascular system with a higher risk of death in this group. In such patients there is an overactivation of renin-angiotensin-aldosterone system, which promotes an increase in the expression of angiotensin-converting enzyme – 2 that acts as a receptor for the SPIKE protein expressed by the virus and enables the interaction between the host cell and Severe Acute Respiratory Syndrome Coronavirus 2. This process of infection causes a hyperinflammatory state that increases the inflammatory markers of cardiac injury. Hence, an adequate understanding and clinical guidance regarding the monitoring, and controlling the damage in these patients is essential to avoid worsening of their clinical condition and to prevent death.